Prevalence and patterns of antimicrobial resistance in salmonella enterica serovar Typhi and Salmonella enterica serovar Paratyphi, Bangladesh - Nuzhat, Shafina Nowshin (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of M.Sc in Biotechnology, 2016.